2014
DOI: 10.1007/s10640-014-9815-7
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Benchmarking Regulation: Revisiting the Efficiency of Environmental Standards

Abstract: The conventional economic argument favors the use of market-based instruments over 'command-and-control' regulation. This viewpoint, however, is often limited in the description and characteristics of the latter; namely, environmental standards are often portrayed as lacking structured abatement incentives. Yet contemporary forms of commandand-control regulation, such as standards stipulated via benchmarking, have the potential to be efficient. We provide a first formal analysis of environmental standards base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The TC has a Total Allowable Catch, Total Allowable Effort, or Total Allocable Habitat Impact which can be a hard cap or 'soft' cap. The goal could also be a vessel-level benchmark, based on a technological, scientific, or industry-specific bycatchtarget catch ratio rather than historical ratio (see Weishaar, 2007;Gerigk et al, 2015;and Goulder et al, 2019 for environmental pollution) or "yardstick" management, in which the bycatch of comparable vessels is used to infer a vessel's attainable bycatch level (see Shleifer, 1985 for environmental pollution and industry regulation). These approaches have largely been developed for and applied to environmental pollution, and are the basis of consideration as an incentives-based approach to bycatch mitigation.…”
Section: Bycatch Creditsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TC has a Total Allowable Catch, Total Allowable Effort, or Total Allocable Habitat Impact which can be a hard cap or 'soft' cap. The goal could also be a vessel-level benchmark, based on a technological, scientific, or industry-specific bycatchtarget catch ratio rather than historical ratio (see Weishaar, 2007;Gerigk et al, 2015;and Goulder et al, 2019 for environmental pollution) or "yardstick" management, in which the bycatch of comparable vessels is used to infer a vessel's attainable bycatch level (see Shleifer, 1985 for environmental pollution and industry regulation). These approaches have largely been developed for and applied to environmental pollution, and are the basis of consideration as an incentives-based approach to bycatch mitigation.…”
Section: Bycatch Creditsmentioning
confidence: 99%
“…5 Relative credits can also be defined in terms of a performance benchmark, such as a target bycatch reduction per vessel (cf. Weishaar, 2007;Gerigk et al, 2015;Goulder et al, 2019;and Kotchen and Segerson, 2019 in environmental economics) or a "yardstick" (cf. Shleifer, 1985 in the economics of regulation literature).…”
Section: Absolute and Relative Bycatch Creditsmentioning
confidence: 99%
“…The ERF signifies that the government formulates environmental protection targets, gives sufficient time and space to the enterprises for implementation, and provides different incentives according to the implementation of ER [26][27][28]. Under this inspiration, more and more studies have found that there are differences in the impact of ER with different degrees of flexibility on enterprise business performance [29][30][31]. Ren et al (2018) divides ER into three categories: command-and-control regulation (CCR), namely emission standards, emission permits and other mandatory ER; Market-based regulation (MBR) is the ER designed to encourage polluters to reduce pollution, such as sewage charge; Voluntary regulation (VR) refers to the relatively loose ER, such as public opinion, negotiation and so on [32].…”
Section: The Moderating Role Of Erfmentioning
confidence: 99%